ANALISIS PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP LOYALITAS KONSUMEN PADA CV. HARWI PRATAMA - Rahajeng Cahyaning Putri Cipto; Yulian Puspita Huda (Jurnal GeoEkonomi, 2020)
This study aims to determine and analyze whether there is an influence of product, price, promotion and location to customer’s loyalty in CV. Harwi Pratama. The research method used descriptive quantitative research with primary data as the source of data. The sampling technique used saturated samples so that the number of samples is the total population which are 89 respondents and the data was processed with SPSS 20 program. Data analysis techniques in this study consisted of F test, t test and multiple linear regression analysis test. The result of research are : (1) product, price, and promotion influence the costumer loyalty simultaneously in CV. Harwi Pratama, (2) the product not influence the costumer loyalty partially, but price and promotion are influence the consumer loyalty partially in CV. Harwi Pratama, (3) among product, price, and promotion, the price is the most influence the costumer loyalty in CV. Harwi Pratama.